The Idea of Merit: Delineation and Challenges. - Clavero García, Sergio R. (Philosophia, 2023)
The idea of merit is at the core of intense contemporary debate related to social justice in general and meritocracy in particular. In this paper, I aim to differentiate the notion of merit from two other notions with which it is often mistakenly identified, namely the concepts of talent and achievement. Here, I define "merit" as the value of an action that 1) is imputable to a subject's free conduct, 2) implies some sort of effort, and 3) is oriented towards a good. Merit so understood is a valuable phenomenon considered from various perspectives, and therefore the subject who has it deserves to be properly recognized. But, more importantly, this merit is valuable in a sense that is different from the value attached to talent and achievement. We should therefore try to recognize the three of them according to their specificity. I conclude by signaling some problems and limitations associated with the idea of merit that, on the one hand, contribute to the aforementioned confusion and, on the other hand, show that the principle of merit must not be absolutized to the detriment of other forms of value (including talent and achievement).